2001
DOI: 10.1007/s005350170114
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic polyangiitis complicated with massive intestinal bleeding

Abstract: Microscopic polyangiitis (MPA) is associated with renal dysfunction, in most cases, and occasionally with pulmonary hemorrhage. However, massive intestinal bleeding is a rare manifestation. We report a case of MPA in a man who developed arterial bleeding in the small intestine. A 74-year-old man was admitted after enduring a fever for 4 weeks. Laboratory examination revealed leucocytosis with neutrophil predominance, and renal dysfunction was noted. He did not respond to treatment with antibiotics, and the wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 20 publications
(16 reference statements)
0
12
0
1
Order By: Relevance
“…Based on definitions agreed by the Consensus Conference, we confirmed the diagnosis of MPA in our patient with clinical symptoms, elevated p-ANCA testing and histopathological findings of skin and lung biopsy. The presence of ANCA can be very helpful for the diagnosis of MPA, because ANCA is known to be frequently found in MPA, WG and ChurgStrauss Syndrome (11)(12)(13). Anti-MPO ANCA pathogenicity has been established in animal models and a recent report describes transplacental transfer of these antibodies in humans resulting in pulmonary hemorrhage and renal involvement in neonates (13).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on definitions agreed by the Consensus Conference, we confirmed the diagnosis of MPA in our patient with clinical symptoms, elevated p-ANCA testing and histopathological findings of skin and lung biopsy. The presence of ANCA can be very helpful for the diagnosis of MPA, because ANCA is known to be frequently found in MPA, WG and ChurgStrauss Syndrome (11)(12)(13). Anti-MPO ANCA pathogenicity has been established in animal models and a recent report describes transplacental transfer of these antibodies in humans resulting in pulmonary hemorrhage and renal involvement in neonates (13).…”
Section: Discussionmentioning
confidence: 99%
“…However, the conference report also commented that direct demonstration of certain pathologic processes noted in the definitions was not necessarily required in order to make a diagnosis. According to the revised Japanese criteria for the diagnosis of MPA put forward by the National Study Group of Angiitis, the diagnosis of 'definite MPA' is made in the existence of one of the two following conditions: MPO-ANCA is detected in patients presenting with both rapidly progressive glomerulonephritis (RPGN) and pulmonary hemorrhage or histological evidence is demonstrated in patients presenting with more than any two of the following three symptoms: (I) RPGN, (II) pulmonary hemorrhage and (III) other symptoms, such as purpura, subcutaneous hemorrhage, gastrointestinal bleeding and mononeuritis multiplex (1,11,12). Our patient satisfied the second criteria for definite MPA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[14,30] While gastrointestinal bleeding occurs in up to 21-29% of patients [52,53], massive hemorrhage is rare. [54] Angiographic studies, although not routinely performed, have shown arterial aneursyms [54,55] as a potential source of bleeding. Other gastrointestinal manifestations such as colonic ulcerations [56], intestinal ischemia [52,57], and bowel perforation [52] have been reported.…”
Section: Gastrointestinal Manifestationsmentioning
confidence: 99%
“…3,4 Although gastrointestinal tract complications are not uncommon, massive hematochezia or melena is very rare in these patients. 5 Antineutrophil cytoplasmic autoantibody (ANCA) has been reported to play a major role in the pathogenesis of crescentic GN. 6 Although ANCA-negative pauci-immune GN has been described, the incidence of this feature is low.…”
Section: Introductionmentioning
confidence: 99%